The Malay dilemma revisted race dynamics in modern Malaysia - M. Bakri Musa (Mohammad Bakri Musa) (Merantau Publisher, 1999)
The Malay Dilemma Revisited is a critical and balanced analysis of Malaysia's preferential race policy and its impact on the nation's delicate race dynamics and economy. Unlike America's affirmative action, Malaysia's version is far more aggressive and pervasive and has been remarkably successful in creating a sizable and stable Bumiputra (indigenous group) middle class. The price tag is significant: distortion of freemarket dynamics and consequent inefficiency. Perversely, the policy impairs rather than strengthens Bumiputras' ability to compete.In contrast to quotas and other set-aside programs that are the hallmark of the current policy, the writer presents an alternative strategy aimed primarily at enhancing Bumiputra competitiveness. The proposed approach would not negatively impact the economy nor interfere with the freemarket. Equally important, it would not arouse resentment from other Malaysians. The first objective would be to modernize the nation's archaic educational system to emphasize English, mathematics, the sciences, and technical training. Secondly, the influences of religious and royal institutions must be curtailed, and the rates of urbanization and population growth reduced.The primary objective is in enhancing competitiveness, not on meeting arbitrarily picked numerical goals and targets.